Investigating the role of feedstock properties and process conditions on products formed during the hydrothermal carbonization of organics using regression techniques. (July 2015) - Li, Liang; Flora, Joseph R.V.; Caicedo, Juan M.; Berge, Nicole D.
Highlights: Hydrothermal carbonization data were collected from the literature. Regression techniques were used to build statistical models. Regression techniques used include multiple linear regression and regression trees. Process conditions are more influential on yield and liquid and gas-phase carbon. Feedstock type is more influential on solid carbon, energy, and normalized carbon. Abstract: The purpose of this study is to develop regression models that describe the role of process conditions and feedstock chemical properties on carbonization product characteristics. Experimental data were collected and compiled from literature-reported carbonization studies and subsequently analyzed using two statistical approaches: multiple linear regression and regression trees. Results from these analyses indicate that both the multiple linear regression and regression tree models fit the product characteristics data well. The regression tree models provide valuable insight into parameter relationships. Relative weight analyses indicate that process conditions are more influential to the solid yields and liquid and gas-phase carbon contents, while feedstock properties are more influential on the hydrochar carbon content, energy content, and the normalized carbon content of the solid.